1944
DOI: 10.1007/bf02547326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deodorization and antioxidants on the stability of lard

Abstract: Summary DEODORIZATION produced no appreciable increase in the stability of steam‐rendered lard but significantly increased the stability of kettlerendered lard. A substantial increase in the stability of lard was produced by tocopherol, regardless of whether it was added as a pure compound, as a concentrate, or as a tocopherol‐bearing oil. Accelerated tests showed that this increase was more than doubled when small amounts of synergists also were added. Deodorization of the lard prior to addition of the synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1945
1945
1988
1988

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…NDGA is particularly good as an antioxidant to prevent rancidity of both vegetable and animal fats (61,159,222,255,202). It is also effective in protecting against rancidity in bacon (277), fish (275, 288), fish oils (38, 101), and walnuts (58).…”
Section: Stereochemistry Of the Lignans And Their Interrelationsmentioning
confidence: 99%
“…NDGA is particularly good as an antioxidant to prevent rancidity of both vegetable and animal fats (61,159,222,255,202). It is also effective in protecting against rancidity in bacon (277), fish (275, 288), fish oils (38, 101), and walnuts (58).…”
Section: Stereochemistry Of the Lignans And Their Interrelationsmentioning
confidence: 99%
“…Hydroxy acids, lactones and related oxygenated material was removed from 275 g samples of butteroil by steam deodorization which was carried on for 6 hr at 170 C using the apparatus and technique described by Riemenschneider et al (6). The deodorized oil was dried over CaC12 before removal of sterols, monoand diglycerides.…”
Section: Steam Deodorizationmentioning
confidence: 99%
“…Riemenschneider et al (21) reported that deodorization increased the stability (determined by the active oxygen method) of kettle-rendered lard but had little effect on the steam-rendered lard. The peroxide content of the lards was not reported, but it is conceivable that the former lard would have a higher peroxide content than the latter.…”
Section: Deaeration and Deodorizationmentioning
confidence: 99%